Developing and Implementing School-based Curriculum in Teaching English - suciati anandes (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
This study aims to investigate and explore school-based curriculum in teaching English at One Elementary School related to the curriculum policy and curriculum instructional of English as a local content in Elementary School. This case-study research employed interview, observation, document analysis and logbook to collect the data about the development and implementation of school-based curriculum (SBC) in teaching English at one elementary. The participants of this study are vice-principal of curriculum affair, teacher of English and student. Evidence from all data sources shows that between the development and implementing are not balance because the instructional documents, facilities, teaching-learning process are not supported each other. In conclusion, all of the aspects in developing and implementing SBC in teaching English at Elementary School should be reviewed and improved.